2021
DOI: 10.1200/jco.2021.39.15_suppl.2599
|View full text |Cite
|
Sign up to set email alerts
|

Real-world pan-cancer landscape of frameshift mutations (FSM) and their role in predicting responses to immune checkpoint inhibitors (ICI) in patients (pts) with tumors with low tumor mutational burden (TMB).

Abstract: 2599 Background: Pembrolizumab was recently approved in tumors with TMB ≥10 mut/Mb. FSM can complement TMB in predicting ICI responses. We obtained a real-world dataset of genomic alterations from 250,813 samples to examine the distribution of TMB and FSM across a variety of malignancies. We then conducted a multi-institutional retrospective review of pts treated with ICI. Methods: Database samples were sequenced by Foundation Medicine using hybrid capture genomic profiling to evaluate all classes of genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…47,53 Furthermore, we have previously shown that INDELs can complement TMB in predicting outcomes to ICI, especially in microsatellite stable/TMB-low tumors. 54 Similarly, our previous work, alongside other studies, highlighted the potential predictive value of TILs in identifying both response and survival benefit. 44,55,56 This study serves as a proof of concept but is compounded by multiple limitations.…”
Section: Discussionsupporting
confidence: 53%
“…47,53 Furthermore, we have previously shown that INDELs can complement TMB in predicting outcomes to ICI, especially in microsatellite stable/TMB-low tumors. 54 Similarly, our previous work, alongside other studies, highlighted the potential predictive value of TILs in identifying both response and survival benefit. 44,55,56 This study serves as a proof of concept but is compounded by multiple limitations.…”
Section: Discussionsupporting
confidence: 53%
“…That said, TMB testing does not account for the immunological alterations imposed by genetic defects other than single nucleotide mutations, such as indels and frameshift mutations. Based on a recent pan‐cancer analysis, frameshift mutations may indeed predict ICI sensitivity in patients with solid tumors bearing a low TMB 43 . Hence, the current approach to measure tumor immunogenicity based on genetic alterations in cancer cells has substantial room for improvement.…”
Section: Immunological Biomarkersmentioning
confidence: 99%